Zodiac [videorecording (Blu-Ray)] - Gyllenhaal, Jake, 1980-; Ruffalo, Mark; Downey, Robert, Jr., 1965-; Edwards, Anthony, 1962-; Cox, Brian, 1946-; Koteas, Elias, 1961-; Logue, Donal, 1966-; Lynch, John Carroll, 1963-; Mulroney, Dermot; Medavoy, Mike; Messer, Arnold W.; Fischer, Bradley J.; et al. (Paramount, 2009)
Robert Graysmith is a socially awkward newspaper cartoonist. He becomes obsessed with the Zodiac, a serial killer whom was murdering people in the San Francisco area. The publicity-hungry Zodiac starts writing cryptic letters to the papers regarding the unsolved murders. He latches onto columnist Paul Avery who has the crime beat and gets overly involved with the investigation. Lead investigator, David Toschi and his partner, William Armstrong, have their hands full with the investigation and the intense interest that the story is generating. Based on actual events that occurred in the 1960s and 1970s.